2020
DOI: 10.1002/dneu.22739
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of glial wrapping: A new hypothesis

Abstract: Animals are able to move and react in numerous ways to external stimuli. Thus, environmental stimuli need to be detected, information must be processed and finally an output decision must be transmitted to the musculature to get the animal moving. All these processes depend on the nervous system which comprises an intricate neuronal network and many glial cells. In the last decades, a neurono-centric view on nervous system function channeled most of the scientific interest toward the analysis of neurons and ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 108 publications
0
16
0
Order By: Relevance
“…This separation then results in a reduction of ephaptic coupling and thus electric noise during neuronal signal transmission. This might represent a further evolutionary advantage towards the development of myelin 33 .…”
Section: Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…This separation then results in a reduction of ephaptic coupling and thus electric noise during neuronal signal transmission. This might represent a further evolutionary advantage towards the development of myelin 33 .…”
Section: Controlmentioning
confidence: 99%
“…Indeed, swimming speed in copepods does not correlate with myelination 32 . This suggests that wrapping glial cells perform additional tasks than just the acceleration of axon potential propagation speed 33 .…”
mentioning
confidence: 99%
“…Oligodendrocytes are glycolytic cells that can provide myelinated axons with lactate or pyruvate for the generation of ATP 5,6,10 . Surprisingly, Drosophila revealed that the metabolic support of axons by associated glia preceded the evolution of myelin in vertebrates 11,12 . In non-myelinating species, notably in Drosophila larvae 13,14 and in lamprey 15 , the axon-associated glial cells that lack myelin accumulate lipid droplets, which are well-known energy reserves 16,17 .…”
Section: Mainmentioning
confidence: 99%
“…Interestingly, compacted myelin is not found in invertebrates but similar morphological specializations have been identified in several invertebrate species such as copepods, earthworms, or shrimps (Davis, Weatherby, Hartline, & Lenz, 1999;Günther, 1976;Roots & Lane, 1983;Xu & Terakawa, 1999). Therefore, it appears possible that the evolutionary origin of myelin formation might have to be placed before the split of invertebrates and vertebrates (see Rey, Zalc, & Klämbt, 2020 for further information, this issue). This is also supported by the molecular mechanisms that regulate simple wrapping in the segmental nerves of the Drosophila PNS.…”
Section: Wrapping Gliamentioning
confidence: 99%